Facile construction of non-precious iron nitride-doped carbon nanofibers as cathode electrocatalysts for proton exchange membrane fuel cells - Palaniselvam, Thangavelu; Kannan, Ramaiyan; Kurungot, Sreekumar (Chemical Communications, 2011)
We demonstrate a facile construction of iron nitride-doped carbon nanofiber by effectively utilizing the existing slit pores and rough edges along the inner wall of the substrate as originated by virtue of its cup-stack structure for effectively increasing the number of active sites and consequently the oxygen reduction activity.

From waste paper basket to solid state and Li-HEC ultracapacitor electrodes: a value added journey for shredded office paper - Puthusseri, Dhanya; Aravindan, Vanchiappan; Anothumakkool, Bihag; Kurungot, Sreekumar; Madhavi, Srinivasan; Ogale, Satishchandra (Small, 2014)
Hydrothermal processing followed by controlled pyrolysis of used white office paper (a globally collectable shredded paper waste) are performed to obtain high surface area carbon with hierarchical pore size distribution. The BET specific surface area of such carbon is 2341 m 2 g(-1). The interconnected macroporous structure along with the concurrent presence of mesopores and micropores makes the material ideal for ultracapacitor application. Such waste paper derived carbon (WPC) shows remarkable performance in all solid-state supercapacitor fabricated with ionic liquid-polymer gel electrolyte. At room temperature, the material exhibits a power density of 19 000 W kg(-1) with an energy capability of 31 Wh kg(-1). The Li-ion electrochemical capacitor constructed using WPC as cathode also shows an excellent energy storage capacity of 61 Wh kg(-1)

Fe(III) phytate metallogel as a prototype anhydrous, intermediate temperature proton conductor - Aiyappa, Harshitha Barike; Saha, Subhadeep; Wadge, Pritish; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Science, 2015)
A proton conducting metallogel [FNPA; ferric nitrate (FN)-phytic acid (PA)] is synthesized by immobilizing a protogenic ligand (phytic acid) using iron(III) nitrate in DMF. The xerogel shows high proton conductivity of 2.4 x 10(-2) S cm(-1) at 120 degrees C, the best value known among all metal organic materials (MOMs). Marking the first such attempt in MOMs, an electrode made using the xerogel showed a power density of 0.94 mW cm(-2) at 0.6 V under dry fuel cell conditions.

Fe2P4O12-carbon composite as a highly stable electrode material for electrochemical capacitors - Soni, Roby; Kurungot, Sreekumar (New Journal of Chemistry, 2019)
Supercapacitors are important energy storage devices for high power applications. Carbon materials, metal oxides and conducting polymers have been known to show capacitive charge storage but transition metal phosphates are not as well-known as electrode materials in supercapacitors. In this study, an iron cyclotetraphosphate (Fe2P4O12)-carbon composite has been synthesized and demonstrated as an electrode material for supercapacitors. The Fe2P4O12-carbon composite has been thoroughly characterized by X-ray photoelectron spectroscopy, Raman spectroscopy, X-ray diffraction, electron microscopy, etc. The composite shows predominant capacitive behaviour only in acidic medium; its charge storage properties are relatively poor in alkaline medium, indicating the important role of H+ in the charge storage mechanism. The composite shows a capacitance of 251 F g(-1) at a current density of 1 A g(-1). The composite is highly stable in 0.5 M H2SO4 and does not show any apparent capacitance loss after 9000 charge-discharge cycles recorded at a current density of 5 A g(-1).

Fe3+ stabilized 3D cross-linked glycine-melamine formaldehyde networks as precursor for highly efficient oxygen reduction catalyst in alkaline media - Kottarathil, Shijina; Illathvalappil, Rajith; Nisa, S.; Sailaja, G. S.; Mohamed, Peer A.; Nair, Balagopal N.; Gopinathan, Anilkumar M.; Kurungot, Sreekumar; Yamaguchi, Takeo; Hareesh, U. S. (Materials Letters, 2020)
Development of inexpensive oxygen reduction electrocatalyst with high activity and durability is very important. Herein, iron carbide encapsulated pod-like graphitic carbon structures were prepared by simple pyrolysis involving Fe-glycine complex integrated melamine-formaldehyde resin precursor. The best catalyst among those studied, Fe-Gly 2 MF-C, possessing high degree of graphitization (I-D /I-G = 0.99) and enhanced specific surface area (205 m(2)/g) exhibited the highest ORR activity with a half-wave potential of 0.80 V in alkaline medium through the four-electron reduction pathway. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: fuel cell; Graphitic carbon alloy; Iron carbide; ORR

FeNx/FeSx-anchored carbon sheet-carbon nanotube composite electrocatalysts for oxygen reduction - Bhange, Siddheshwar N.; Soni, Roby; Singla, Gourav; Ajithkumar, T. G.; Kurungot, Sreekumar (ACS Applied Nano Materials, 2020)
Even though various Pt-free electrocatalysts for oxygen reduction reaction (ORR) have been introduced, many of them are found to be active only in alkaline conditions. Considering Nafion, phosphoric acid-doped polybenzimidazole (PBI), and so on as the prominent ionomer membranes, used in the commercially available polymer electrolyte membrane fuel cells (PEMFCs), it becomes important that any development on the Pt-free catalysts should ensure the better ORR performance under acidic conditions. The present work effectively tackles this issue, where an ORR-based catalyst could be prepared with simultaneous incorporation of both Fe-N and Fe-S active sites on in situ generated carbon sheets which are spatially separated by the carbon nanotube (CNT) network. This catalyst shows ability to perform under both acidic and basic conditions. This has been achieved by growing a polyethylenedioxythiophene polymer network in the presence of CNT and melamine followed by its pyrolysis under an inert atmosphere. The catalyst formed at 900 degrees C (PMCNT-900) displays 0.94 V onset potential for ORR under acidic electrolyte conditions, which corresponds to 60 mV overpotential compared to its 40 wt % Pt/C counterpart. Interestingly, in single cell demonstration of Nafion-based PEMFC with PMCNT-900 as the cathode catalyst, the system delivered a maximum power density (PD) of 500 and 275 mW/cm(2) at 60 degrees C under H-2-O-2 and H-2-air feed conditions, respectively. On the other hand, in a single cell test in the anion exchange membrane fuel cell (AEMFC) mode, a maximum power density of 65 mW/cm(2) at 50 degrees C could be achieved with the same cathode catalyst, which is a comparable value obtained while employing Pt/C as the cathode. These results, thus, infer to the efficiency of the catalyst to facilitate ORR under the extreme pH conditions, and particularly its performance under acidic condition reveals its prospect as a potential Pt-free electrocatalyst to serve in the Nafion-based systems.
Keywords: carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction; Pt-free ORR

Facile synthesis of CNT interconnected PVP-ZIF-8 derived hierarchically porous Zn/N co-doped carbon frameworks for oxygen reduction dagger - Singla, Gourav; Bhange, Siddheshwar N.; Mahajan, Mani; Kurungot, Sreekumar (Nanoscale, 2021)
In this work, a strategy has been adopted to construct an architecture through the coordination of polyvinylpyrrolidone (PVP) and a monodisperse zeolitic imidazolate framework (ZIF-8), which was entwined by carbon nanotubes (CNTs) firstly, followed by a pyrolysis process to obtain the hybrid catalyst. The meticulous design of the hybrid material using CNTs to interconnect the PVP assisted ZIF-8 derived porous carbon frameworks together produces a hierarchical pore structure and dual-heteroatom (Zn/N) doping (Zn-N/PC@CNT). Without further acid treatment, the hybrid material prepared after pyrolysis at 900 degrees C (PVP-ZIF-8@CNT-900) has been demonstrated as an efficient non-precious metal catalyst for the oxygen reduction reaction (ORR) with its superior stability compared to the commercial 20 wt% Pt/C catalyst in alkaline media. The catalyst shows better performance towards the ORR, with its more positive onset and half-wave potentials (E-onset = 0.960 V vs. RHE and E-1/2 = 0.795 V vs. RHE) than the counterpart system which is free of both CNT and PVP. The high performance of the hybrid catalyst can be ascribed to the co-existence of dual-active sites with hierarchical pore structures originating from the synergistic effects between Zn/N co-doped porous carbon and CNTs. We further demonstrated the single-cell performance by using the homemade system as the cathode catalyst for the Alkaline Exchange Membrane Fuel Cell (AEMFC) system, which showed a maximum power density of 45 mW cm(-2) compared to 60 mW cm(-2) obtained from the 40 wt% Pt/C catalyst.

F-doped nickel cobalt oxide-carbon composite electrocatalysts paired with mechanically robust anion-conducting chitosan membranes for flexible and rechargeable zinc-air batteries - Kurian, Maria; Ranganath, Suresha P.; Vijayakumar, Vidyanand; Sivadasan, Sneha; Kurian, Rachna Maria; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Energy Materials, 2024)
High-performing, cost-effective electrocatalysts and anion-conducting polymer electrolyte membranes are essential for realizing commercially affordable zinc-air batteries (ZABs). In this context, the present work deals with the development of a bifunctional electrocatalyst and an anion-exchange quasi-solid-state electrolyte membrane (based on quaternary ammonium group-grafted chitosan) for demonstrating flexible and rechargeable ZABs. The electrocatalyst composed of NiCoO2 nanoparticles supported on a carbon framework showcased substantial advancements in its ability to catalyze both oxygen reduction and evolution reactions (ORR and OER) due to the heteroatom doping by fluorine. For instance, the optimized electrocatalyst (F-NCO-ADC-600) exhibited an onset potential of 0.96 V vs RHE with a half-wave potential of 0.83 V vs RHE for ORR, a comparable performance with the state-of-the-art Pt/C (1.0 and 0.86 V vs RHE, respectively). On a similar note, the same catalyst also displayed an overpotential of 340 mV vs RHE for OER at a current density of 20 mA cm(-2), close to that of a standard RuO2 catalyst (337 mV vs RHE). In the context of polymer electrolytes, the quaternary ammonium-group-grafted chitosan membrane depicted superior ionic conductivity, liquid electrolyte uptake, and mechanical properties, thereby proving to be an efficient anion-conducting polymer electrolyte membrane. The realistic application of the developed electrocatalyst and the polymer electrolyte membrane is demonstrated in the ZAB prototypes. The assembled rechargeable ZAB (RZAB) delivered a power density of 207 mW cm(-2) and maintained high-rate capability and cycling stability, notably in a flexible configuration (f-RZABs). Thus, this work provides a strategy for the rational design of anion-exchange membranes and bifunctional electrocatalysts for f-RZABs.
Keywords: anion-conducting polymer electrolytemembrane; F-doping; flexible and rechargeable zinc-air batteries(f-RZABs); oxygen evolution reaction(OER); oxygen reduction reaction (ORR)